125th Anniversary Review: Barley research in relation to Scotch whisky production: a journey to new frontiers. Issue 1 (14th January 2015) - Bringhurst, T. A.
<x xml:space="preserve">Abstract</x> Human experience with barley has been well established for several millennia and barley research has been fundamental to our understanding of raw materials for malting, brewing and distilling. Distillers have long been indebted to malting, brewing and distilling researchers for information on barley (and malt) relevant to their operations. Originally distilling barley research was focussed on the parameters defining barley quality and plant performance, but it has developed to further our understanding of the properties and genetics of barley and malt. Through the years, several strategic milestones can be identified showing a progression of related research themes, culminating in our current state of knowledge of barley. These include the development of the fermentability method, together with the biochemistry and enzymology underlying starch and cell wall hydrolysis, which resulted in a greater understanding of processing properties and subsequent improvements in performance. Ethyl carbamate is a barley‐derived carcinogen present in a range of potable spirits, which has been a concern for distillers; the identification of the genetic marker for the barley precursor epiheterodendrin laid the foundations for the application of modern (non‐GMO) genetics to developing improved barley varieties, which will benefit the whole supply chain. Together these approaches underline the mutual interdependence of applied research and genetic approaches in achieving substantial advances in our knowledge. Copyright © 2015 The Institute of Brewing & Distilling